Impaired Subcortical Detection of Auditory Changes in Schizophrenia but Not in Major Depression. (11th April 2019) - Gaebler, Arnim Johannes; Zweerings, Jana; Koten, Jan Willem; König, Andrea Anna; Turetsky, Bruce I; Zvyagintsev, Mikhail; Mathiak, Klaus
Abstract: The mismatch negativity is a cortical response to auditory changes and its reduction is a consistent finding in schizophrenia. Recent evidence revealed that the human brain detects auditory changes already at subcortical stages of the auditory pathway. This finding, however, raises the question where in the auditory hierarchy the schizophrenic deficit first evolves and whether the well-known cortical deficit may be a consequence of dysfunction at lower hierarchical levels. Finally, it should be resolved whether mismatch profiles differ between schizophrenia and affective disorders which exhibit auditory processing deficits as well. We used functional magnetic resonance imaging to assess auditory mismatch processing in 29 patients with schizophrenia, 27 patients with major depression, and 31 healthy control subjects. Analysis included whole-brain activation, region of interest, path and connectivity analysis. In schizophrenia, mismatch deficits emerged at all stages of the auditory pathway including the inferior colliculus, thalamus, auditory, and prefrontal cortex. In depression, deficits were observed in the prefrontal cortex only. Path analysis revealed that activation deficits propagated from subcortical to cortical nodes in a feed-forward mechanism. Finally, both patient groups exhibited reduced connectivity along this processing stream. Auditory mismatch impairments in schizophrenia already manifest at the subcortical level. Moreover, subcortical deficits contribute to the well-known cortical deficits and show specificity for schizophrenia. In contrast, depression is associated with cortical dysfunction only. Hence, schizophrenia and major depression exhibit different neural profiles of sensory processing deficits. Our findings add to a converging body of evidence for brainstem and thalamic dysfunction as a hallmark of schizophrenia.